Le Crétacé inférieur de la marge atlantique portugaise: biostratigraphie, organization séquentielle, evolution paléogéographique - Rey, J. (2008)
This paper gives a short description of main stratigraphic unities from the early Cretaceous in Estremadura and Algarve, with their lithological, sedimentological and paleontological characteristics. The distribution of facies enable to propose a paleogeographic frame including eroded high areas and sedimentary low areas roughly parallel to the present coast. The early Cretaceous from Estremadura is splited up into three megasequences each one with regressive then transgressive tendencies: this fact must be connected with the leading action of distensive, slow or sudden, movements. Beyond the hercynian fault of Messejana, Algarve presents a different sedimentary evolution during the early Cretaceous.